2015
DOI: 10.1007/s13358-015-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Neogene molluscs, shallow marine paleoenvironments, and chronostratigraphy of the Guajira Peninsula, Colombia

Abstract: The Neogene sedimentary fill of the Cocinetas Basin in northern Colombia preserves a rich record of marine invertebrates and can be analyzed in the context of a high-resolution stratigraphy and excellent chronostratigraphy. Molluscan fossils are highly diverse and often well preserved, offering a window into the rapidly changing paleoenvironments and biogeography of northern South America during parts of the Early to Middle Miocene and latest Pliocene to Pleistocene. Before the evolutionary and biogeographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 22 publications
1
70
0
1
Order By: Relevance
“…Rollins (1965), however, accepted that none of the macrofauna collected were diagnostic for age, although they seem to suggest a Pliocene age (following current biostratigraphic knowledge). As noted above, Rollins's (1965) identifications and interpretation are in doubt and are critically assessed by Hendy et al (2015) in this issue. Rollins (1965 p. 59) agreed with Renz (1960) that the base of the Castilletes was in the Miocene, but argued that the top of the unit was Pliocene on the basis of its stratigraphic position (Fig.…”
Section: Geological Settingmentioning
confidence: 97%
See 2 more Smart Citations
“…Rollins (1965), however, accepted that none of the macrofauna collected were diagnostic for age, although they seem to suggest a Pliocene age (following current biostratigraphic knowledge). As noted above, Rollins's (1965) identifications and interpretation are in doubt and are critically assessed by Hendy et al (2015) in this issue. Rollins (1965 p. 59) agreed with Renz (1960) that the base of the Castilletes was in the Miocene, but argued that the top of the unit was Pliocene on the basis of its stratigraphic position (Fig.…”
Section: Geological Settingmentioning
confidence: 97%
“…While these 'species' are largely supportive of a Late Miocene age (following current biostratigraphic knowledge), the identifications and interpretation of Rollins (1965) need to be revised. A review of macropalaeontological evidence for the age of the Neogene units of the Cocinetas Basin is provided by Hendy et al (2015) in this issue. The foraminiferal biotas that occur in the lower and upper parts of the Jimol Formation are associated with the Miogypsina günteri and the Miogypsina intermedia biozones (Renz 1960).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the Uitpa Formation was deposited in an open water environment (Becker and Dusenbury, 1958;Rollins, 1965;Thomas, 1972;Hendy et al, 2015). Becker and Dusenbury (1958) The extant species corresponding to such sharks prefer environments with deep-water near the continental slope (Fig.…”
Section: Paleoenvironment and Paleobathymetrymentioning
confidence: 92%
“…While an Oligocene to early Miocene age was proposed by Becker and Dusenbury (1958) based on benthic foraminifera, Lockwood (1965) and Rollins (1965) suggested an early Miocene age (Aquitanian) based on foraminifera and ostracods. More recently, an early Miocene to earliest middle Miocene age was proposed by Hendy et al (2015) based on mollusks and stratigraphic relations. The outcrop studied herein is located close to the Uitpa village ( Fig.…”
Section: Geological and Stratigraphical Settingmentioning
confidence: 99%